DIFFERENCES IN ANTHROPOMETRIC MEASUREMENTS BETWEEN LIBYAN AND SERBIAN PASSENGER CAR DRIVERS AND CRANE OPERATORS - Spasojević-Brkić, Vesna K; Veljkovic, Zorica; Essdai, Ahmed; Brkic, Aleksandar (Journal of Applied Engineering Science, 2019)
This paper is a part of ongoing research on passenger car drivers’ and crane operators’ anthropometric measurements data collected in aim to make comparison, explore ergonomic adaptation and finally improve safety. It represents one of the rare explorations containing the Libyan male drivers and crane operators’ data, and accordingly it is one of the first researches in anthropometric field on Libyan population. Herein, statistical analysis on Libyan 300 male drivers and 50 crane operators collected data shows that male drivers are taller, and have higher sitting height as well as upper leg length values, while crane operators have slightly wider shoulders and hips. Both Libyan groups have the same arm and foot lengths. Apart of Libyan male car drivers and crane operators, research includes also and Serbian car drivers (921 Serbian male drivers) compared with crane operators (83 crane operators). Obtained data show that Serbian male car drivers have significantly larger standing height and upper leg length values, while foot length is significantly lower for drivers than for crane operators. Passenger vehicle and crane cabins designers can benefit from this survey.